Determinants of successful - Jordaan, Gideon Francois (My University, 2011)
Globalisation is of great concern for manufacturing industries in developing countries. The need to gain and keep a competitive advantage in local markets is becoming a key issue experienced by most manufacturers in South Africa. This is especially true in the Electrical Power Sector of South Africa, when considering products from abroad can be imported for much cheaper than the cost of local manufacturing. Given this context, this research focuses on understanding determinants that affect relationship marketing with parastatals in South Africa, as a strategy to gain a competitive advantage. Standardised open-ended interviews were conducted with five (5) employees in the procurement department of a parastatal and five (5) employees from a supplier, to explore the determinants that affect relationship marketing with parastatals in South Africa. The findings of the research suggest that the relationship between a supplier and a parastatal is affected by various determinants. Suppliers seek to do business with parastatals because it is profitable. In order for suppliers to be considered by parastatals to engage in a relationship, they need to comply with government regulations. Thereafter, determinants that affect the continuation of the relationship are complete customer satisfaction; meeting and exceeding customer expectations; the continuous creation of customer value; willingness to cooperate in achieving the parastatal’s objectives; and lastly the supplier’s ability to negotiate win-win scenarios if the two parties are experiencing conflict situations. Although the findings from this research cannot be generalised to all parastatals in South Africa, they do suggest that relationship marketing is a complex phenomenon and many determinants need to be considered in order to be successful
MBA - WBS
Keywords: Relationship marketing; Marketing; Parastatals